The Exploration of the experiences and perceptions of service providers on the implementation of the Amendments to the Criminal Law (Sexual Offenses and Related Matters) Amendment Act 13 of 2021: The case of statutory rape in Johannesburg, Gauteng - Doodhnath, Sirishka (University of the Witwatersrand, Johannesburg, 2024)
This study aims to explore service providers’ perceptions and experiences regarding the implementation of the Criminal Law (Sexual Offences and Related Matters) Amendment Act 13 of 2021 in South Africa. The study examined the regulations concerning the age of consent for sexual activity involving minors, which are considered essential in addressing statutory rape. Using a qualitative research approach and exploratory study design, the study sought to gain an in-depth understanding of service providers on the effectiveness of the Act in addressing statutory rape and related issues. 12 service providers who have worked on the Amended Act were recruited and sampled for the study with the assistance of the Department of Community Safety. The department provided the researcher with a list of multi-disciplinary team professionals involved in the Victim Empowerment program. The study employed semi- structured interviews using interview guides to collect data from all service providers involved in the implementation of the Act. Thematic analysis was used to analyse the data and to identify recurring themes. The study findings offer insights that can assist policymakers in addressing the challenges and gaps in the implementation of the Act, with the goal of protecting minors and combating statutory rape in South Africa.
A research report Submitted in fulfillment of the requirements for a Master of Arts in Social Work, In the Faculty of Humanities , School of Human And Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Statutory rape; Sexual abuse; Criminal Law (Sexual Offenses and Related Matters) Amendment Act No; 13 of 2021 service providers; social workers; sexual assaul; SDG-16: Peace, justice and strong institutions